Preparation method and application of heat-absorbing and heat-conducting silicone adhesive and heat-absorbing and heat-conducting silicone adhesive
By preparing a thermally conductive silicone glue containing low viscosity vinyl silicone oil, high viscosity vinyl silicone oil, hydrogen-containing silicone oil, modified acrylic resin and catalyst, adding spherical hydroxy iron powder coated with alumina and aluminum nitride powder, and finally adding spherical alumina, the instability caused by electromagnetic interference and excessive heat in smart wearable devices is solved, and effective wave absorbing thermal control of the device is achieved.
Patent Information
- Application Number
- CN202311669517.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-07
- Publication Date
- 2025-04-11
AI Technical Summary
Due to instability caused by electromagnetic interference and excessive heat in smart wearable devices, the prior art thermal conductivity silicone glue cannot meet the needs of wave absorbing heat.
The silicone liquid is formed by using low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, hydrogen-containing silicone oil, modified acrylic resin and catalysts, and the silicone gel liquid is formed by stirring and vacuum debubbing process, and spherical hydroxy iron powder coated with alumina and aluminum nitride powder are added, and finally spherical alumina is added to prepare thermally conductive silicone glue.
Effective control of electromagnetic wave radiation and thermal energy of smart devices is achieved, and unstable equipment caused by electromagnetic interference and excessive heat is avoided.
Smart Images

Figure CN119799002A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application, and wave-absorbing heat-conducting silicone adhesive, and in particular to a preparation method and application, and wave-absorbing heat-conducting silicone adhesive. Background Art
[0002] With the rapid development of electronic information technology, various electromagnetic radiations are generated inside smart wearable devices. The electromagnetic fields inside highly integrated devices interfere with each other, causing the devices to become unstable after long-term operation, which urgently needs to be improved. Summary of the invention
[0003] The purpose of the present invention is to provide a preparation method and application of wave-absorbing and heat-conducting silicone glue, and the wave-absorbing and heat-conducting silicone glue is applied to smart wearable devices to play the role of wave absorption and heat conduction, thereby solving the shortcomings of the prior art.
[0004] The present invention provides the following scheme:
[0005] A method for preparing a wave-absorbing and heat-conducting silicone adhesive, comprising:
[0006] The raw materials are added into a stirring kettle for stirring, and a vacuum degassing process is performed to form a silica gel liquid;
[0007] The raw materials include at least: low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, hydrogen-containing silicone oil, modified acrylic silicone resin, and a catalyst;
[0008] The viscosity range of the low-viscosity vinyl silicone oil is 100-300 mPa.s, the viscosity range of the high-viscosity vinyl silicone oil is 5000-7000 mPa.s, and the viscosity range of the hydrogen-containing silicone oil is 10-60 mPa.s;
[0009] Adding alumina-coated spherical hydroxy iron powder into the silica gel solution and stirring;
[0010] Aluminum nitride powder is then added and stirred, and a vacuum degassing process is performed;
[0011] Finally, spherical alumina is added and stirred to obtain thermally conductive silicone adhesive.
[0012] Furthermore, in terms of mass fractions, there are 90 parts of low-viscosity vinyl silicone oil, 10 parts of high-viscosity vinyl, 5 parts of hydrogenated silicone oil, 45 parts of modified acrylic silicone resin, 1 part of catalyst, and the remaining component is isopropyl alcohol.
[0013] Furthermore, the catalyst is a platinum catalyst.
[0014] Further, spherical hydroxy iron powder coated with alumina was added to the silica gel solution and stirred for one hour; spherical alumina was added and stirred for 2 hours.
[0015] Furthermore, the preparation process of the alumina-coated spherical hydroxy iron powder is as follows: according to the mass fractions, 24 parts of ammonia water, 700 parts of spherical hydroxy iron powder and 12 parts of aluminum sulfate are added to every 2000 parts of deionized water solution, and the mixture is ultrasonically dispersed to obtain a mixed solution, the mixed solution is heated in a water bath and stirred for reaction at a temperature of 1 000 °C, washed with ethanol and then centrifuged, dried in an oven and then annealed to obtain the alumina-coated spherical hydroxy iron powder.
[0016] Furthermore, the time for mixed ultrasonic dispersion is 10-20 minutes, the mixed solution is heated to 80-90°C in a water bath, the time for heat preservation and stirring reaction is 1h-2h, and it is dried in an oven at 40-60°C for 15h-20h. The annealing temperature is 380°C and the annealing time is 1.5-3h.
[0017] Furthermore, the mixing and ultrasonic dispersion are carried out for 15 minutes to obtain a mixed solution, the mixed solution is heated in a water bath at a temperature of 85°C, and the mixed solution is stirred and kept warm for 1.5 hours. After being washed with ethanol several times, the mixture is centrifuged, dried in an oven at 50°C for 16 hours, and annealed at 380°C for 2 hours to obtain spherical hydroxyl iron powder coated with alumina.
[0018] Furthermore, the mesh number of the aluminum nitride is 3000 mesh, and the amount used is 15 to 60 parts by mass fraction. The mesh number of the aluminum oxide powder is 1250 mesh, and the amount used is 15 to 60 parts by mass fraction.
[0019] A wave-absorbing heat-conducting silicone adhesive is prepared by adopting the preparation method of the wave-absorbing heat-conducting silicone adhesive.
[0020] The wave-absorbing and heat-conducting silicone adhesive is used as a filling material in smart devices.
[0021] Compared with the prior art, the present invention has the following advantages: the present invention uses wave-absorbing and heat-conducting silicone glue to fill the device components and the shell, thereby achieving control of the electromagnetic wave radiation and thermal energy of the device, thereby avoiding instability caused by electromagnetic interference and excessive heat in smart wearable devices or other smart electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 It is a flow chart of a method for preparing a wave-absorbing and heat-conducting silicone adhesive. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In the prior art, the preparation method of silicone glue generally comprises the following steps:
[0026] 1. Prepare raw materials: prepare the required organosilicon compounds and cross-linking agents.
[0027] 2. Mixing raw materials: Mix the organosilicon compound and the cross-linking agent together in a certain proportion to ensure uniform mixing.
[0028] 3. Adding additives: According to needs, appropriate amounts of fillers, thickeners and other additives can be added to change the properties of the colloid.
[0029] 4. Stirring and mixing: Use a stirring device to stir the mixture thoroughly to ensure that all ingredients are evenly dispersed in the solution
[0030] 5. Remove bubbles: Remove bubbles from the mixture by vacuum treatment or other methods to avoid adverse effects on the performance of the final product.
[0031] 6. Curing reaction: Place the mixture at an appropriate temperature for a curing reaction to form an elastic solid state.
[0032] 7. Cutting: If needed, the cured silicone rubber can be cut into the required size and shape using cutting equipment.
[0033] The thermally conductive silicone adhesive prepared by the above steps only has ordinary conventional functions and does not have wave absorption and heat conduction functions, and cannot meet the wave absorption and heat conduction requirements of smart devices, so it needs to be improved.
[0034] like Figure 1 The method for preparing the wave-absorbing heat-conducting silicone adhesive shown comprises:
[0035] Step S1, adding raw materials into a stirring tank for stirring, and performing a vacuum degassing process to form a silica gel liquid;
[0036] The raw materials include at least: low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, hydrogen-containing silicone oil, modified acrylic silicone resin, and a catalyst;
[0037] Specifically, according to the mass proportions, there are 90 parts of low-viscosity vinyl silicone oil, 10 parts of high-viscosity vinyl, 5 parts of hydrogen-containing silicone oil, 45 parts of modified acrylic silicone resin, 1 part of catalyst, and the remaining ingredients are isopropanol, and the catalyst is a platinum catalyst.
[0038] Specifically, spherical hydroxy iron powder coated with alumina was added to the silica gel liquid and stirred for one hour; spherical alumina was added and stirred for 2 hours.
[0039] The viscosity range of the low-viscosity vinyl silicone oil is 100-300 mPa.s, the viscosity range of the high-viscosity vinyl silicone oil is 5000-7000 mPa.s, and the viscosity range of the hydrogen-containing silicone oil is 10-60 mPa.s;
[0040] Step S2, adding alumina-coated spherical hydroxy iron powder to the silica gel liquid and stirring. By adding alumina-coated spherical hydroxy iron powder, the uniformity of iron powder dispersion and heat resistance can be improved, so that it can still maintain good magnetic properties in a high temperature environment. At the same time, since the surface of the hydroxy iron powder is alumina, the dielectric constant of the hydroxy iron powder is reduced, which is conducive to the entry of high-frequency electromagnetic waves into the interface to improve the absorption performance, and the surface of the alumina improves the thermal conductivity of the hydroxy iron powder, reduces the oxidizability of the iron powder, and reduces the viscosity of the liquid, so that the final product has good stability and heat resistance, is not easy to fail in a high temperature environment, and enables the sealing material or coating material to work for a long time in a high temperature environment.
[0041] Step S3, adding aluminum nitride powder, stirring, and performing a vacuum degassing process;
[0042] Specifically, the preparation process of the alumina-coated spherical hydroxy iron powder is as follows: according to the mass ratio, 24 parts of ammonia water, 700 parts of spherical hydroxy iron powder and 12 parts of aluminum sulfate are added to every 2000 parts of deionized water solution, and the mixture is ultrasonically dispersed to obtain a mixed solution, the mixed solution is heated in a water bath and stirred for reaction at a temperature of 1 000 °C, washed with ethanol and then centrifuged, dried in an oven and then annealed to obtain the alumina-coated spherical hydroxy iron powder.
[0043] Exemplarily, the time for mixed ultrasonic dispersion is 10-20 minutes, preferably 15 minutes, the mixed solution is heated in a water bath to 80-90°C, preferably 85°C, and the time for heat preservation and stirring reaction is 1h-2h, preferably 1.5h, and the mixture is dried in an oven at 40-60°C for 15h-
[0044] 20h, preferably 15h, the annealing temperature is 380°C, and the annealing time is 1.5-3h, preferably 2h.
[0045] Exemplarily, the mesh size of aluminum nitride is 3000 mesh, and the usage amount is 15 to 60 parts by mass fraction; the mesh size of aluminum oxide powder is 1250 mesh, and the usage amount is 15 to 60 parts by mass fraction.
[0046] The use of alumina-coated spherical hydroxy iron powder to prepare wave-absorbing and heat-conducting silicone adhesive can improve the uniformity of iron powder dispersion and heat resistance, so that it can still maintain good magnetic properties in high-temperature environments. At the same time, since the surface of the hydroxy iron powder is covered with alumina, the dielectric constant of the hydroxy iron powder is reduced, which is conducive to the entry of high-frequency electromagnetic waves into the interface to improve the absorption performance. The surface of alumina also improves the thermal conductivity of the hydroxy iron powder, reduces the oxidizability of the iron powder, and reduces the viscosity of the liquid, so that the final product has good stability and heat resistance, is not easy to fail in a high-temperature environment, and enables the sealing material or coating material to work for a long time in a high-temperature environment. This method can be used to prepare silicone adhesive.
[0047] Step S4, finally add spherical alumina and stir to obtain thermally conductive silicone adhesive. Since spherical alumina has good high temperature resistance, corrosion resistance and mechanical strength, adding spherical alumina during the preparation process can improve the stability of the thermally conductive silicone adhesive material. This allows the material to maintain good physical and chemical properties under long-term use or in harsh environments, and can fully guarantee the wave absorption performance and thermal conductivity of the wave-absorbing thermally conductive silicone adhesive.
[0048] Glossary: Vacuum degassing is a process used to remove bubbles from an object and create a vacuum environment. In this process, the concentration and pressure of gas molecules are reduced by reducing the pressure, so that the bubbles inside the object gradually diffuse, shrink or disappear. As the pressure drops, the tiny bubbles originally existing inside the component will be squeezed out or dissolved, thereby improving product quality and reliability.
[0049] Ultrasonic dispersion: Ultrasonic dispersion is a process that uses the power of ultrasound to disperse solid particles or droplets into a liquid. In this process, ultrasound generates high-frequency vibrations, which cause particles or droplets to be subjected to shear, impact, and dissociation forces, thereby achieving uniform dispersion in the solvent. When ultrasound propagates into the solvent, stable compressible and expansive regions are formed. These regions can cause local temperature increases, vaporization, and condensation, and generate strong micro-flows that can break the interaction forces between aggregated substances and disperse them into the solvent.
[0050] Based on the process flow of the above embodiment, wave-absorbing thermally conductive silicone adhesive is prepared, and the final product is wave-absorbing thermally conductive silicone adhesive, which can be used as a filling material in smart devices.
[0051] Embodiment 1:
[0052] Weigh according to the mass fraction, stir 90 parts of low-viscosity vinyl silicone oil, 10 parts of high-viscosity vinyl silicone oil, and 1 part of platinum catalyst at 80°C for 1 hour at a stirring speed of 800rpm to form a uniform liquid, then heat to 105°C and add 45 parts of acrylic silicone resin and 5 parts of hydrogen-containing silicone oil, stir at a stirring speed of 1200rpm for 1.5 hours, then cool to 60°C and vacuum to remove bubbles. Then add 700 parts of alumina-coated spherical hydroxy iron powder and stir for 1 hour, then add 15 parts of aluminum nitride powder and stir, then vacuum to remove bubbles; finally, add 15 parts of spherical alumina, stir for 2 hours, and then discharge.
[0053] In this embodiment, the viscosity range of low-viscosity vinyl silicone oil is 100-300 mPa.s, and the preferred values are 100, 150, 200, and 300 mPa.s; the viscosity range of high-viscosity vinyl silicone oil is 5000-7000 mPa.s, and the preferred values are 5000, 5500, 6500, and 7000 mPa.s; the viscosity range of hydrogen-containing silicone oil is 10-60 mPa.s;
[0054] Embodiment 2:
[0055] Weigh according to the mass fraction, weigh 90 parts of low-viscosity vinyl silicone oil, 10 parts of high-viscosity vinyl silicone oil, and 1 part of platinum catalyst, stir at 80°C for 1 hour, stirring at 800rpm to form a uniform liquid, then heat to 105°C and add 45 parts of acrylic silicone resin and 5 parts of hydrogen-containing silicone oil, stir at 1200rpm for 1.5 hours, then cool to 60°C and vacuum to remove bubbles. Then add 700 parts of alumina-coated spherical hydroxy iron powder and stir for 1 hour, add 30 parts of aluminum nitride powder and stir, then vacuum to remove bubbles; finally, add 90 parts of spherical alumina, stir for 2 hours, and then discharge.
[0056] In this embodiment, the viscosity range of low-viscosity vinyl silicone oil is 100-300 mPa.s, and the preferred values are 100, 150, 200, and 300 mPa.s; the viscosity range of high-viscosity vinyl silicone oil is 5000-7000 mPa.s, and the preferred values are 5000, 5500, 6500, and 7000 mPa.s; the viscosity range of hydrogen-containing silicone oil is 10-60 mPa.s;
[0057] Embodiment 3:
[0058] Weigh according to the mass fraction, weigh 90 parts of low-viscosity vinyl silicone oil, 10 parts of high-viscosity vinyl silicone oil, and 1 part of platinum catalyst, stir at 80°C for 1 hour, stirring at 800rpm to form a uniform liquid, then heat to 105°C and add 45 parts of acrylic silicone resin and 5 parts of hydrogen-containing silicone oil, stir at 1200rpm for 1.5 hours, then cool to 60°C and vacuum to remove bubbles. Then add 700 parts of alumina-coated spherical hydroxy iron powder and stir for 1 hour, add 45 parts of aluminum nitride powder and stir, then vacuum to remove bubbles; finally, add 75 parts of spherical alumina, stir for 2 hours, and then discharge.
[0059] In this embodiment, the viscosity range of low-viscosity vinyl silicone oil is 100-300 mPa.s, and the preferred values are 100, 150, 200, and 300 mPa.s; the viscosity range of high-viscosity vinyl silicone oil is 5000-7000 mPa.s, and the preferred values are 5000, 5500, 6500, and 7000 mPa.s; the viscosity range of hydrogen-containing silicone oil is 10-60 mPa.s;
[0060] Embodiment 4:
[0061] Weigh according to the mass fraction, weigh 90 parts of low-viscosity vinyl silicone oil, 10 parts of high-viscosity vinyl silicone oil, and 1 part of platinum catalyst, stir at 80°C for 1 hour, stirring at 800rpm to form a uniform liquid, then heat to 105°C and add 45 parts of acrylic silicone resin and 5 parts of hydrogen-containing silicone oil, stir at 1200rpm for 1.5 hours, then cool to 60°C and vacuum to remove bubbles. Then add 700 parts of alumina-coated spherical hydroxy iron powder and stir for 1 hour, add 60 parts of aluminum nitride powder and stir, then vacuum to remove bubbles; finally, add 60 parts of spherical alumina, stir for 2 hours, and then discharge.
[0062] In this embodiment, the viscosity range of low-viscosity vinyl silicone oil is 100-300 mPa.s, and the preferred values are 100, 150, 200, and 300 mPa.s; the viscosity range of high-viscosity vinyl silicone oil is 5000-7000 mPa.s, and the preferred values are 5000, 5500, 6500, and 7000 mPa.s; the viscosity range of hydrogen-containing silicone oil is 10-60 mPa.s;
[0063] Performance Testing:
[0064] The silicone adhesives of Examples 1 to 4 were coated on an aluminum plate with a side length of 180 mm × 180 mm × 3 mm, and the coating thickness was 3 mm. The reflectivity was tested according to the detection method in GJB2038A-2011 "Test Method for Reflectivity of Radar Absorbing Materials". The thermal conductivity of the silicone adhesive coating with a thickness of 3 mm was tested using the transient plane heat source method. The obtained performance parameters are shown in Table 1
[0065]
[0066] Those skilled in the art will appreciate that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those skilled in the art in the field to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined.
[0067] It should be noted that certain words are used in this specification and claims to refer to specific components. Those skilled in the art should understand that different manufacturers and producers may use different terms to refer to the same component. This specification and claims do not use the difference in terms as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction.
[0068] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0069] In addition, those skilled in the art will appreciate that, although some embodiments described herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present invention and form different embodiments. For example, any one of the embodiments claimed in the claims can be used in any combination in the embodiments of the present invention.
[0070] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0071] In this application, the word "exemplary" is used to mean "used as an example, illustration, or description." Any embodiment described in this application as "exemplary" is not necessarily to be construed as being preferred or advantageous over other embodiments. The following description is given to enable any technician in the field to implement and use the present application. In the following description, details are listed for the purpose of explanation. It should be understood that a person of ordinary skill in the art can recognize that the present application can be implemented without using these specific details. In other instances, well-known structures and processes will not be elaborated in detail to avoid obscuring the description of the present application with unnecessary details. Therefore, the present application is not intended to be limited to the embodiments shown, but is consistent with the widest scope consistent with the principles and features disclosed in the present application.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a wave-absorbing and heat-conducting silicone adhesive, characterized in that: include: The raw materials are added into a stirring kettle for stirring, and a vacuum degassing process is performed to form a silica gel liquid; The raw materials include at least: low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, hydrogen-containing silicone oil, modified acrylic silicone resin, and a catalyst; The viscosity range of the low-viscosity vinyl silicone oil is 100-300 mPa.s, the viscosity range of the high-viscosity vinyl silicone oil is 5000-7000 mPa.s, and the viscosity range of the hydrogen-containing silicone oil is 10-60 mPa.s; Adding alumina-coated spherical hydroxy iron powder into the silica gel solution and stirring; Aluminum nitride powder is then added and stirred, and a vacuum degassing process is performed; Finally, spherical alumina is added and stirred to obtain thermally conductive silicone adhesive.
2. The method for preparing the wave-absorbing heat-conducting silicone adhesive according to claim 1, characterized in that: In terms of mass percentage, there are 90 parts of low-viscosity vinyl silicone oil, 10 parts of high-viscosity vinyl, 5 parts of hydrogen-containing silicone oil, 45 parts of modified acrylic silicone resin, 1 part of catalyst, and the remaining ingredient is isopropyl alcohol.
3. The method for preparing the wave-absorbing and heat-conducting silicone adhesive according to claim 1, characterized in that: The catalyst is a platinum catalyst.
4. The method for preparing the wave-absorbing heat-conducting silicone adhesive according to claim 1, characterized in that: Alumina-coated spherical hydroxy iron powder was added to the silica gel solution and stirred for one hour; spherical alumina was added and stirred for 2 hours.
5. The method for preparing the wave-absorbing heat-conducting silicone adhesive according to claim 1, characterized in that: The preparation process of alumina-coated spherical hydroxy iron powder is as follows: according to the mass fractions, 24 parts of ammonia water, 700 parts of spherical hydroxy iron powder and 12 parts of aluminum sulfate are added to every 2000 parts of deionized water solution, and the mixture is ultrasonically dispersed to obtain a mixed solution, the mixed solution is heated in a water bath and stirred for reaction at a temperature of 1 000 °C, washed with ethanol and then centrifuged, dried in an oven and then annealed to obtain alumina-coated spherical hydroxy iron powder.
6. The method for preparing the wave-absorbing heat-conducting silicone adhesive according to claim 5, characterized in that: The time for mixed ultrasonic dispersion is 10-20 minutes, the mixed solution is heated to 80-90°C in a water bath, the time for heat preservation and stirring reaction is 1h-2h, and it is dried in an oven at 40-60°C for 15h-20h. The annealing temperature is 380°C and the annealing time is 1.5-3h.
7. The method for preparing the wave-absorbing and heat-conducting silicone adhesive according to claim 6, characterized in that: The mixing and ultrasonic dispersion time is 15 minutes to obtain a mixed solution, the mixed solution is heated in a water bath at a temperature of 85°C, and the mixed solution is stirred and kept warm for 1.5 hours. After multiple washings with ethanol, centrifugal separation is performed, and the mixture is dried in an oven at 50°C for 16 hours and annealed at 380°C for 2 hours to obtain spherical hydroxy iron powder coated with alumina.
8. The method for preparing the wave-absorbing heat-conducting silicone adhesive according to claim 1, characterized in that: The mesh number of the aluminum nitride is 3000 mesh, and the usage amount is 15 to 60 parts by mass fraction. The mesh number of the aluminum oxide powder is 1250 mesh, and the usage amount is 15 to 60 parts by mass fraction.
9. A wave-absorbing and heat-conducting silicone adhesive, characterized in that: The wave-absorbing and heat-conducting silicone adhesive is prepared by the method for preparing the wave-absorbing and heat-conducting silicone adhesive according to any one of claims 1 to 8.
10. Use of the wave-absorbing and heat-conducting silicone adhesive according to claim 9 as a filling material in smart devices.